26. Mednarodno posvetovanje »Komunalna energetika 2017«: 9. do 11. maj 2017 Maribor, Slovenija - Pihler, Jože (2017)
26th Expert Meeting »Power Engineering 2017«: May 9th to 11th 2017 Maribor, Slovenia. At the Faculty of Electrical Engineering, Computer Science and Informatics, the University of Maribor, for the twenty-sixth year, we are organizing an international consultation, Komunalna energija - energetsko oskrbo. Over the years, several hundred papers dealt with various topics related to energy supply at the level of local communities, the Republic of Slovenia and beyond. The papers also discussed the latest research achievements in this field. Since energy supply is a fundamental need of a modern human being, we will continue to work with the organization of the consultation in the future. The special focus of this year's consultation is on "Energy Management". In the field of regulation, the Slovenian standard SIST EN ISO 50001 "Energy Management System" is adopted, which aims to enable organizations to establish the systems and procedures needed to improve energy efficiency, including energy efficiency, use and consumption. The invited lectures are entirely dedicated to this topic. The Energy Directorate of the Ministry of Infrastructure will present regulations, current practices and guidelines for the future in the field of energy management. The Energy Agency plays an important role in the supply of all types of energy, with electricity, natural gas and heat. Most of the experience is currently in the management of electricity, the management of natural gas has been going on for some time, and heat management is in the initial phase. Experts from individual fields will present the situation in Slovenia. The references of the consultation are presented in six thematic sections, namely: Energy impacts on climate and the environment; Energy apparatus apparatus and networks; Energy efficiency and energy management; ICT in energy; Financing of energy projects and Student strand.
Keywords: energy